Modelos agrometeorológicos estatísticos de previsão de produtividade e qualidade para cana-de-açúcar - Marcari, Marcos Antonio [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The climate is the important factor of influence for sugarcane and its study is fundamental for understanding the climatic requirements of the crop. The estimate is made with historical data and is a current condition, as the forecast is the estimate made for the future, ie, with current available data simulate a future state. The present work aimed developing regional agro-meteorological models to make the yield forecasting of tons of sugarcane per hectare (TCH) and quality in relation to total recoverable sugar (ATR) of sugarcane in a monthly scale. We used monthly climatological data (air temperature, Precipitation, Water Deficiency and Surplus, Potential and Actual evapotranspiration, Soil Water Storage, Solar Global irradiation) of the previously year to forecast TCH and ATR of the next year using multiple linear regression. The combination of monthly climatological data was made searching a small mean absolute percentage error possible with p-value less than 0.05, and models with greater possible anticipation. Data of 12 years of Jaboticabal, a major sugarcane producer in the State of São Paulo, were used for analysis, being the period from 2002 to 2009 used for calibration and from 2010 to 2013 for validation. We observed that all models calibrated were significant and accurate, because the higher values of mean absolute percentage error (MAPE) were of 4.06% in the forecasting of the TCH(C) of July. The model calibrated for November had the presence of water deficit variable in every environment, showing the importance of this variable in the crop. Monthly models tested in this work showed significant performances in their forecasting's. For example, the forecast of the TCHMAY in the AB environment (MAPE = 1.89% and R2 adj = 0.90) considering an average value of 90.6 t ha-1 in the region, the model misses about 1.7 t ha-1.In this case the anticipation for forecasting TCHMAY was eight months because the last climatological ...

O clima é o fator importante que influencia a cana-de-açúcar e seu estudo é fundamental para entender as exigências climáticas da safra. A estimativa é feita com dados históricos e representa uma condição atual, já a previsão é a estimativa feita para o futuro, ou seja, com dados disponíveis atuais simular uma condição futura. O presente trabalho teve como objetivo o desenvolvimento de modelos agro-meteorológicos regionais para fazer a previsão da produtividade em toneladas de cana por hectare (TCH) e qualidade da matéria prima em relação á total de açúcar recuperável (ATR) da cana em uma escala mensal. Foram utilizados dados climatológicos mensais (temperatura do ar, precipitação, deficiência e excesso hidricos, evapotranspiração potencial e real do solo, armazenamento de água no solo, radiação solar global) do ano anterior, para prever TCH e ATR do próximo ano por meio de regressão linear múltipla. A combinação de dados climatológica mensal foi feito buscando um menor erro médio percentual absoluto possível com valor-p inferior a 0,05, e modelos com maior antecipação possível. Dados de 12 anos da região de Jaboticabal, de um grande produtor de cana no Estado de São Paulo, foram utilizados para análise, sendo o período de 2002-2009 utilizados para calibração e 2010-2013 para validação. Observou-se que todos os modelos calibrados foram significativos e precisos, pois os maiores valores de erro médio percentual absoluto (MAPE) foram de 4,06% na previsão do TCH (C) de julho. O modelo calibrado para novembro teve a presença de variável déficit hídrico em todos os ambientes, mostrando a importância dessa variável na cultura. Modelos mensais testadas neste trabalho apresentaram desempenhos significativos em sua previsão. Por exemplo, a previsão do TCHMAI no ambiente AB (MAPE = 1,89% e R adj = 0,90), considerando um valor médio de 90,6 t ha-1 na região, o modelo erra cerca de...
Keywords: Balanço hidrológico; Cana-de-açúcar; Climatologia agricola; Meteorologia agricola; Produtividade agrícola; Meteorology